Emotion Processing in Women with Schizophrenia Is Menstrual Cycle Phase and Affective Valence Dependent: An fMRI Study - Mendrek, Adrianna (International Scholarly Research Network, 2012)
Despite a large number of functional neuroimaging investigations of emotion processing in schizophrenia, very few have included women. In the present study 21 schizophrenia and 23 healthy women underwent functional MRI (3T) on two occasions (during the follicular and luteal phase of their menstrual cycle) while viewing blocks of emotionally negative, positive and neutral images. During exposure to negatively charged images patients showed relatively less activations than controls during the luteal phase, but no between-group differences were observed during the follicular phase. In contrast, the exposure to positively valenced material produced no significant interaction, but the main effect of group; schizophrenia patients exhibited less activation than healthy controls during both phases of the menstrual cycle. This is the first study demonstrating that atypical neural activations associated with emotion processing in women diagnosed with schizophrenia depend on the menstrual cycle phase and on the affective valence of presented stimuli.